Estimation of post- mortem interval by some biochemical changes of vitreous humor. - Kareem, Saad Kadhum (AL-Kindy College Medical Journal, 2015)
Background:No previous Iraqi study was done on the estimation of post mortem interval (PMI) from the medico-legal point of view; depending on the biochemical changes of vitreous humor.Objectives:To find out the relationship between some biochemical changes in vitreous humor and post mortem interval.To find out a new formula for estimation of PMI from some biochemical changes in vitreous humor.Method:The study was conducted on one hundred twenty two cases referred to the medico-legal institute in Sulaimani province during the period between 1st of February and 30th of July 2012.Complete classical autopsy was performed for each case and vitreous humor was collected at autopsy from the posterior chamber of the eye and the samples after collection were immediately transported for biochemical analysis.Only crystal clear vitreous humor was used for analysis.Results:With increasing postmortem interval; the vitreous humor potassium (K+) and calcium (Ca++) were increased. The changes of potassium and calcium were significantly correlated with the postmortem interval. The studied changes in chemical components of vitreous humor after death revealed that potassium had the best linear correlation with the postmortem interval within 40 hours after death and can be estimated by the following equation: (PMI=3.36[k+]-14.35)with standard deviation of±7.44hours.Conclusion:The study showed that vitreous potassium can precisely be used for estimating PMI and proposed a new formula for estimation of PMI which is PMI=3.36[K+]-14.35 that can be used for up to 40 hours with standard deviation of ±7.44hours.